Ultrafast control and opto-optical modulation of extreme ultraviolet light - Bengtsson, Samuel ; 0000-0001-6668-6744; Mauritsson, Johan ; 0000-0002-7289-5072 (Journal of Physics B: Atomic, Molecular and Optical Physics, 2019)
Ultrashort, coherent light pulses in the extreme ultraviolet (XUV) wavelength region are excellent tools for a wide range of experiments. These XUV pulses are in particular used to characterize electron dynamics. Additionally, the high photon energy enables quantum control of short-lived transitions in atoms. These transitions are of interest for ultrafast quantum control as the bandwidth of the control pulses needs to be less than the transition frequency. Coherent XUV pulses would be even more useful if the tools to control and manipulate them existed. Presently, however, no modulators exist for these frequencies, which significantly reduces the number of possible ultrafast optics experiments and applications in the XUV regime. This Ph.D. tutorial addresses this problem and focuses on the control of XUV light in time and space. To enable control of XUV light we have developed a method for opto-optical modulation (OOM), which modulates the phase of XUV light emitted from a gas of atoms. The atoms are resonantly excited with a coherent XUV pulse generated through high order harmonic generation and emit light after the excitation pulse passed. By shifting the resonance frequencies through the AC Stark shift with a non-resonant infrared control pulse, the phase of the emitted light, and therefore its wavefront, is controlled. With OOM the direction of XUV light emitted from noble gases has been controlled, and the temporal dynamics of the emission studied. By varying the delay between the excitation and the control pulse, the time of redirection was controlled, which enabled high signal to noise study of the temporal dynamics of the emission. Furthermore, a proof-of-principle experiment with two control pulses was performed, resulting in a shaped XUV pulse with controlled duration. The technique of OOM presented in this article is still at a very early stage and in order to obtain complete control of the amplitude and phase of the XUV pulses further development is necessary. Such development would present new opportunities for ultrafast XUV quantum control.